Film in contemporary Southeast Asia Cultural Interpretation and Social Intervention - Lim, David C. L.; Yamamoto, Hiroyuki (Taylor & Francis, 2012)
This book discusses contemporary film in all the main countries of Southeast Asia, and the social practices and ideologies which films either represent or oppose. It shows how film acquires signification through cultural interpretation, and how film also serves as a site of contestations between social and political agents seeking to promote, challenge, or erase certain meanings, messages or ideas from public circulation. A unique feature of the book is that it focuses as much on films as it does on the societies from which these films emerge: it considers the reasons for film-makers taking the positions they take; the positions and counter-positions taken; the response of different communities; and the extent to which these interventions are connected to global flows of culture and capital.